A phage cocktail in controlling phage resistance development in multidrug resistant Aeromonas hydrophila with great therapeutic potential. (January 2022) - Yu, Huabo; Zhang, Liang; Feng, Chao; Chi, Teng; Qi, Yanling; Abbas Raza, Sayed Haidar; Gao, Na; Jia, Kaixiang; Zhang, Yang; Fan, Ruining; Cai, Ruopeng; Qian, Aidong; et al.
Absract: Aeromonas hydrophila ( A. hydrophila ) is an opportunistic pathogen of fish-human-livestock, which poses a threat to the development of aquaculture. Lytic phage has long been considered as an effective bactericidal agent. However, the rapid development of phage resistance seriously hinders the continuous application of lytic phages. In our study, a new bacteriophage vB_ AhaP_PZL-Ah8 was isolated from sewage and its characteristics and genome were investigated. Phage vB_ AhaP_PZL-Ah8 has been classified as the member of the Podoviridae family, which exhibited the latent period was about 30 min. As revealed from the genomic sequence analysis, vB_ AhaP_PZL-Ah8 covered a double-stranded genome of 40, 855 bp (exhibiting 51.89% G + C content), with encoding 52 predicted open reading frames (ORFs). The results suggested that the combination of vB_ AhaP_PZL-Ah8 and another A. hydrophila phage vB_ AhaP_PZL-Ah1 could improve the therapeutic efficacy both in vitro and in vivo . The resistance mutation frequency of A. hydrophila cells infected with the mixture phage (vB_ AhaP_PZL-Ah8+ vB_ AhaP_PZL-Ah1) was significantly lower than cells treated with single phage ( P <0.01 ). Phage therapy in vivo showed that the survival rate in the mixture phage treatment group was significantly higher than that in single phage treatment group. Highlights: A novel A . hydrophila phage was isolated, characterized and sequenced. The combination of two A. hydrophila phages could improve the therapeutic efficacy . The combination of two phages could reduce the emergence of phage resistance stains.